2016
DOI: 10.1248/cpb.c15-00922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, <i>in Vivo</i> Anti-inflammatory, and <i>in Vitro</i> Antimicrobial Activity of New 5-Benzofuranyl Fused Pyrimidines

Abstract: Chalcone (3) has been synthesized as a new chalcone derivative bearing benzofuran moiety at 1 position. Such chalcone was used as a model dielectrophile applied to react with some nucleophiles such as 5-amino pyrazoles, 5-amino-1,2,4-triazole, 2-aminobenzimidazole, and 6-uraciles under Michael reaction conditions and resulted in a new series of fused pyrimidines such as pyrazolo[1,5-a]pyrimidines 7a-e, [1,2,4]-triazolo[1,5-a]pyrimidine 9, pyrimido[1,2-a]benzimidazole 11, and synthesis of pyrido[2,3-d]pyrimidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…IR spectra (400-4000 cm −1 ) were performed in KBr disc on the Nicolet iS10 FT-IR spectrometer. 1 H NMR (at 400 MHz) and 13 C NMR (at 100 MHz) spectra were recorded on a Varian Gemini spectrometer using tetramethylsilane (TMS) as an internal standard in deuterated dimethylsulphoxide (DMSOd 6 ). Mass spectra were recorded on a Shimadzu GCMS-QP 1000 EX mass spectrometer at 70 eV at the Regional Center for Mycology and Biotechnology of Al-Azhar University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra (400-4000 cm −1 ) were performed in KBr disc on the Nicolet iS10 FT-IR spectrometer. 1 H NMR (at 400 MHz) and 13 C NMR (at 100 MHz) spectra were recorded on a Varian Gemini spectrometer using tetramethylsilane (TMS) as an internal standard in deuterated dimethylsulphoxide (DMSOd 6 ). Mass spectra were recorded on a Shimadzu GCMS-QP 1000 EX mass spectrometer at 70 eV at the Regional Center for Mycology and Biotechnology of Al-Azhar University.…”
Section: Methodsmentioning
confidence: 99%
“…40 Accordingly, we utilized an eco-friendly method; ultrasonic waves for synthesis of 2-cyano-N'-(4-(piperidin-1-yl)benzylidene) acetohydrazide 3 as a synthon to synthesize novel arylidenes and heteroarylidenes. The newly synthesized compounds were conrmed via spectral analyses such as FT-IR, 1 H NMR, 13 C NMR, and mass spectra. These compounds were evaluated for their antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…The bicyclic moiety containing N1 is essentially planar as there is only an 0.87 (6) dihedral angle between the constituent planes while that containing N5 is less planar with a corresponding dihedral angle of 1.10 (7) . The dihedral angle between the two 6-membered rings is 73.48 (8) . The N2 C6 and N6 C15 bond distances of 1.325 (3) and 1.331 (4) Å are consistent with largely localized double bonds as is the N5 C12 distance of 1.324 (3) Å.…”
Section: X-ray Description Of the Crystal Structure Ofmentioning
confidence: 99%
“…Indeed, these heterocycles possess many active sites that make them favorable precursors for the synthesis of novel heterocyclic molecular systems capable of exhibiting a wide spectrum of activity. Moreover, they are used as antibacterial, [3,4] Tropomyosin receptor kinases (Trks), [5] anticancer, [6,7] anti-inflammatory, [8] and antitumor agents. [9] Recently, Das et al synthesized a series of substituted pyrazolo [1,5-a]pyrimidine derivatives via a green synthetic route, which show potential antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compounds 63 (R 1 = 4-Cl-C6H4, R 2 = 4-H3CO-C6H4), (R 1 = 2-Thienyl, R 2 = 4-F-C6H4) and (R 1 = 2-Thienyl, R 2 = 4-H3CO-C6H4) were reported to have the most active anti-fungal agents against Aspergillus fumigatus. Otherwise, Nassar et al 88 reported that pyrido[2,3-d]pyrimidine 63 (R 1 = 2-Thienyl, R 2 = 4-H3CO-C6H4) showed the most anti-microbial effect against Gram-negative Pseudomonas aeruginosa (Scheme 25, Table 10).…”
Section: Table 8 Synthesis Of Compounds 54a-lmentioning
confidence: 99%